c.2 - Lal Bahadur Shastri National Academy (Mussoorie, 1998)
This book is about Co-operatives: Policy Issues for the SAARC Region published in association with the Centre for Co-operatives and Rural Development, LBS National Academy of Administration.
Keywords: Cooperatives